PERAN KEPALA SEKOLAH SEBAGAI INOVATOR DI SEKOLAH MENENGAH PERTAMA NEGERI KOTA PARIAMAN - Jezi Adrian Putra (Universitas Negeri Padang, 2014)
The goal of this research are to see information aboutthe headmasters role as an innovator. The population is 349teachers and the sample is 83 people that taken by proportional random sampling. The instrument of this research is question with Likert scale modelsthat had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research are the headmasters role as an innovator in SMP Negeri Kota Pariaman stay in good enough category. Key word : headmasters role as an innovator